Perspectives of HER2-targeting in gastric and esophageal cancer. (4th May 2017) - Gerson, James N; Skariah, Sam; Denlinger, Crystal S.; Astsaturov, Igor
ABSTRACT: Introduction : The blockade of HER2 signaling has significantly improved the outlook for esophagogastric cancer patients. However, targeting HER2 still remains challenging due to complex biology of this receptor in gastric and esophageal cancers. Areas covered : Here, we review complex HER2 biology, current methods of HER2 testing and tumor heterogeneity of gastroesophageal cancer. Ongoing and completed clinical research data are discussed. Expert opinion: HER2 overexpression is a validated target in gastroesophageal cancer, with therapeutic implications resulting in prolonged survival when inhibited in the front-line setting. With standardized HER2 testing in gastro-esophageal cancer, the ongoing trials are testing newer agents and combinations including combination of anti-HER2 antibodies with immunotherapy. Clonal heterogeneity and emergence of resistance will challenge our approach to treating these patients beyond the frontline settings.